Reading comprehension difficulties among middle eastern students / Ihab A. Abdulaziz - Ihab, A. Abdulaziz (2012)
Reading is a process that requires effort on the readers’ part if they want to understand what they are reading. A vast amount of research has been devoted to understand processes that contribute to reading comprehension. As part of that research, this study was conducted to explore problems or difficulties faced by 30 Middle Eastern students in the University of Malaya when they read texts in English and the reading strategies used by them. Based on the hypotheses that the students lack of ability to identify main ideas, infer information, deduce meaning from context, elicit specific information or details, guess and make predictions, understand relations between sentences and recognize the author’s purpose, it was found that the major difficulties faced by students are identifying main ideas, deducing meaning from context and eliciting specific information. The results of the study also showed the strategies are to refer to the glossary to understand the meaning of words and refer to the illustration to help them understand the text. In fact, these 30 Middle Eastern students in the University of Malaya, also always read and try to understand in both Arabic as their first language and also in English as their foreign language. Suggestions are made that EFL educators should expose the students to appropriate methods and materials, integrate reading and writing and extend reading courses in their teaching process. The study also recommends that to improve students’ reading comprehension, it has to start during the early stages of reading acquisition because children's oral language comprehension level is much higher than their reading comprehension level.